Assessment of Physical Fitness in Medical Students - Chaudhary, Sailesh; Khadka, Rita; Pandey, Karishma Rajbhandari; Paudel, Bishnu Hari; Shah, Gaurav Jung; Chaudhary, Hiramani Prasad (Journal of Nepalgunj Medical College, 2022)
Introduction: Physical activity promotes cerebral blood flow during cognitive tasks and possibly enhances performance. It is relevant to find relationship between post exercise recovery heart rate (RHR) and resting pulse rate in medical students. Aims: To assess physical fitness in medical students. Methods: In this cross-sectional study, 57 consenting healthy medical students, age 1730 years, underwent 3-Minutes Step Test to assess their physical fitness. Students were divided into four fitness groups based on RHR; good (n=9, RHR=50-84 bpm), satisfactory (n=17, RHR=88-100 bpm), poor (n=12, RHR=102-107 bpm), and very poor (n= 19, RHR=111-157 bpm) groups. The groups were compared using one-way ANOVA. A p<0.05 was considered statistically significant. Results: Results showed that there were few numbers of students who fall in good fitness group (n= 9, Resting pulse rate mean 72.00 ± 9.29) in comparison to satisfactory fitness group (n= 17, Resting pulse rate mean (68.35 ± 5.95), poor fitness group (n= 12, Resting pulse rate mean 75.67 ± 6.88) and very poor fitness group (n=19, Resting pulse rate mean 78.89 ± 7.67). The level of significance between satisfactory fitness group and very poor fitness group, p <0.05 was statistically significant. Conclusion: Most of the medical students fall under very poor fitness group. Satisfactory fitness group have less resting pulse rate in compare to very poor fitness group of medical students.